PRICING WITH CONFIDENCE how to raise prices and stay ahead of inflation, without losing customers. - Holden, Reed K.; Mukherjee, Jeet (JOHN WILEY & SONS, 2022)
"With inflation raging, businesses must raise prices, but there's a problem--how to do it wisely, without losing customers. Pricing with Confidence, Second Edition gives a professional pricing wisdom on how to raise prices in an inflationary world, without alienating customers or hurting sales. It shows managers and salespeople how to kick the price discounting habit they often use as a crutch to close a sale. The book also helps business and product leaders recognize the market the value of what they sell to customers, and how to price accordingly. In ten practical steps, Pricing with Confidence, Second Edition, explains how managers can have both healthy profit margins and robust revenue growth, while staying ahead of inflation."--